A CROSS-SECTIONAL STUDY OF NUTRITIONAL STATUS AND ATOPIC DERMATITIS IN ADOLESCENTS - Effendi, Ida; Diwa, Puti Maharani (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
Atopic dermatitis is the number one disease among the top 10 skin diseases affecting children. Abnormal nutritional status can affect the immune system and increase the risk of infection and allergic diseases, including atopic dermatitis. This study aimed to determine the association between nutritional status and the occurrence of atopic dermatitis in adolescents. An analytic observational study with a cross-sectional design was conducted involving 204 adolescents aged 10–18 years selected through simple random sampling from medical records at Cengkareng Regional General Hospital. Nutritional status was assessed using body mass index-for-age, while the diagnosis of atopic dermatitis was obtained from physicians’ medical records. Data analysis was performed using the Chi-Square test with SPSS. The results showed the study subjects had normal nutritional status (50.5%) and atopic dermatitis (38.7%). Atopic dermatitis was more common in the overweight and obese nutritional status groups (54.2% and 54.8%). There was a significant relationship between nutritional status and the incidence of atopic dermatitis (p=0.000). Nutritional status was significantly associated with the incidence of atopic dermatitis in adolescents.